2020
DOI: 10.1080/09168451.2019.1693252
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol-rich fraction from annatto ameliorates expression of lysyl oxidase in human osteoblastic MG-63 cells

Abstract: Lysyl oxidase (LOX) is required for the formation of bone collagen cross-links. Inactivation of the LOX gene in osteoblasts by DNA methylation and JAK signaling has been reported to cause loss of cross-links and an increased risk of fractures. Tocotrienols (T3s) have proven benefits on bone strength, but their potential effects on LOX remain largely unknown. Thus, the present study investigates the in vitro effects of T3s on LOX expression in human osteoblastic MG-63 cells. Results indicated that Tocotrienol-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recent studies showed that TRF, extracted from annatto was the most effective and significantly increased lysyl oxidase (LOX) expression, which is required for the formation of bone collagen crosslinks. Inactivation of the LOX gene in osteoblasts has been reported to cause loss of cross-links and an increased risk of fractures [47]. Therefore, VCO and TRF have potential in maintaining the bone strength by reducing and increasing the osteoclastic and osteoblastic activities, respectively.…”
Section: Young Modulusmentioning
confidence: 99%
“…Recent studies showed that TRF, extracted from annatto was the most effective and significantly increased lysyl oxidase (LOX) expression, which is required for the formation of bone collagen crosslinks. Inactivation of the LOX gene in osteoblasts has been reported to cause loss of cross-links and an increased risk of fractures [47]. Therefore, VCO and TRF have potential in maintaining the bone strength by reducing and increasing the osteoclastic and osteoblastic activities, respectively.…”
Section: Young Modulusmentioning
confidence: 99%